A intersetorialidade nas políticas públicas (saúde, assistência social e educação) como estratégia de enfrentamento da pobreza na região do Jalapão no Estado do Tocantins - Araujo, Gislene Ferreira da Silva (2017)
This dissertation has by object the intersectionality of welfare’s public polices, social assistance and education, as strategy of confrontation of poverty in Jalapão’s region in State of Tocantins. The question that orientate this analysis is the capture of how has been setting up the intersectionality of welfare’s public polices, social assistance and education, as strategy of confrontation of poverty in Jalapão’s region and to what extent this articulation is performed and materializes in the management of services, programs, projects and benefits in cities from this region, localized in state of Tocantins. The larger objective is understand and explain how the articulation intersectional occur at logic of social police’s management that relate the conditionalities of “Bolsa Familia” Program in cities from the Jalapão’s region and what possibility of this polices, by the form that be lead in cities can satisfy the needs of population in situation of poverty and extreme poverty. The Inquire that give origins for this study is documental and bibliography, take by consult from documents relative to welfare’s police, assistance social and education existents in this cities researched and by information available in web pages too. The results points a large distance between the legal precept and the principles explained, each one from organic laws of these polices. What is found in documents searched and in information accessed is that cities need to advance in your management projects to get closer of the achievements already regulated in scope of social rights in Brazil. Yet, it is perceived much “adjustment” and improvisations for answer the requirements put in agreements between the federation entities, which almost clarify the unprofessionalization and the emptying from the qualify work and in line with the prerogatives of polices of State.